Downregulation of Leucine-Rich Repeat-Containing 8A Limits Proliferation and Increases Sensitivity of Glioblastoma to Temozolomide and Carmustine - Rubino, Sebastian; Bach, Martin D.; Schober, Alexandra L.; Lambert, Ian H.; Mongin, Alexander A. (Frontiers in Oncology, 2018)
Background: Glioblastoma (GBM) is the most common primary malignant brain tumor in adults. Ubiquitously expressed volume-regulated anion channels (VRAC) are thought to play a role in cell proliferation, migration, and apoptosis. VRAC are heteromeric channel complexes assembled from proteins belonging to the leucine-rich repeat-containing family 8 (LRRC8A through E), among which LRRC8A plays an indispensable role. In the present work, we used an RNAi approach to test potential significance of VRAC and LRRC8A in GBM survival and sensitivity to chemotherapeutic agents. Methods: Primary GBM cells were derived from a human surgical tissue sample. LRRC8A expression was determined with qRT-PCR and downregulated using siRNA. The effects of LRRC8A knockdown on GBM cell viability, proliferation, and sensitivity to chemotherapeutic agents were determined using MTT and Coulter counter assays. Cell cycle progression was further explored using fluorescence-activated cell sorting analysis of propidium iodide-stained cells. Results: Temozolomide, carmustine, and cisplatin reduced GBM cell survival with the IC50 values of ~1250, 320, and 30 µM, respectively. Two of three tested gene-specific siRNA constructs, siLRRC8A_3 and siLRRC8A_6, downregulated LRRC8A expression by >80% and significantly reduced GBM cell numbers. The most potent siLRRC8A_3 itself reduced viable cell numbers by ≥50%, and significantly increased toxicity of the sub-IC50 concentrations of temozolomide (570 µM) and carmustine (167 µM). In contrast, the effects of siLRRC8A_3 and cisplatin (32 µM) were not additive, most likely because cisplatin uptake is VRAC-dependent. The results obtained in primary GBM cells were qualitatively recapitulated in U251 human glioblastoma cell line. Conclusions: Downregulation of LRRC8A expression reduces GBM cell expansion and increases sensitivity to the clinically used temozolomide and carmustine. These findings indicate that VRAC represents a potential target for the treatment of GBM, alone or in combination with the current standard-of-care.